Vsevedno pripovedovanje v pripovednoteoretskih omrežjih - Koron, Alenka (Primerjalna književnost, 2011)
Since modernism, omniscient narration has often been attacked, but it has rarely been studied and understood, despite its role in narrative discourse and metadiscourse. This article examines the polemics between two narrative theorists, Jonathan Culler and Meir Sternberg, who diverge on the nature of narrative omniscience and the usefulness of the concept for the study of narration. It also deals with the discussion of omniscient narration and the omniscient narrator by Matias Martínez and Janko Kos to shed light on the background and scope of their approaches and to point to the characteristics of omniscient narration that speak for its "long duration" in the world of narrative.
Keywords: naratologija; narratology; pripovedovanje; pripovedna struktura; vsevedni pripovedovalec; poeta vates